2019
DOI: 10.1111/ejh.13308
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation and dynamics of cytomegalovirus and Epstein‐Barr virus after rabbit antithymocyte globulin and cyclosporine for aplastic anemia

Abstract: Objectives This study aimed to identify the natural course of cytomegalovirus (CMV)/Epstein‐Barr virus (EBV) after rabbit antithymocyte globulin and cyclosporine (rATG‐CsA) for aplastic anemia (AA). Methods In 113 prospectively observed AA patients treated with rATG‐CsA, the CMV/EBV cohort was classified into two groups by baseline viremic status: no viremia (CMV‐G1, n = 112; EBV‐G1, n = 98) and the presence of viremia (CMV‐G2, n = 1; EBV‐G2, n = 13). Results In CMV‐G1, the mean CMV load increased up to 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In previous studies, severe aplastic anemia (SAA) patients undergoing unrelated donor transplantation received rituximab in combination with ATG-containing conditioning regimens to prevent EBV reactivation ( 27 , 48 ). Previous studies showed that the risk factors for EBV activation were predominantly related to the degree of T cell depletion or impairment, including mismatch between donor and recipient, T cell depletion from graft, degree and duration of immunosuppression, and use of ATG or alemtuzumab (anti-CD52) ( 41 , 45 , 49 51 ). Furthermore, we found CMV activation, HLA mismatch and cGVHD were independent risk factors for EBV reactivation, while the usage of rituximab was proved to prevent EBV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, severe aplastic anemia (SAA) patients undergoing unrelated donor transplantation received rituximab in combination with ATG-containing conditioning regimens to prevent EBV reactivation ( 27 , 48 ). Previous studies showed that the risk factors for EBV activation were predominantly related to the degree of T cell depletion or impairment, including mismatch between donor and recipient, T cell depletion from graft, degree and duration of immunosuppression, and use of ATG or alemtuzumab (anti-CD52) ( 41 , 45 , 49 51 ). Furthermore, we found CMV activation, HLA mismatch and cGVHD were independent risk factors for EBV reactivation, while the usage of rituximab was proved to prevent EBV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…A partial response was determined as no longer meeting the criteria for SAA and having transfusion independence for >8 weeks 3 , 14 . An analysis of glycosylphosphatidylinositol‐deficient granulocytes was performed by flow cytometry outlined in our previous report 13 . Bone marrow samples of healthy controls were collected from healthy donor for allogeneic BM transplantation following written consent.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis and severity of idiopathic AA were assessed according to previous reports. 10 , 11 Patients received IST consisting of rabbit ATG (Thymoglobulin; Genzyme-Sanofi, Lyon, France) and cyclosporine (n = 7) as previously described 12 , 13 or cyclosporine monotherapy (n = 4). Patients with SAA received the combination of ATG and cyclosporine as the standard treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the use of ATG [39], a higher titer of CMV-IgG in recipients before allo-HSCT [40], and the titer of the human leukocyte antigen allele type [41] have also been associated with CMV reactivation. ATG use or dose may increase CMV reactivation in patients with aplastic anemia and renal transplantation [42][43][44][45]. More aggressive CMV prophylaxis, such as letermovir, should be considered in patients with these risk factors, which present before allo-HSCT or may occur during allo-HSCT.…”
Section: Plos Onementioning
confidence: 99%